The legacy of the Soviet agricultural research system for the Republics of Central Asia and The Caucasus - Morgounov, A.; Zuidema, L. (La Haya (Holanda), 2001)
Sumario (En)
Ilus.; 35 ref.
Keywords: INVESTIGACION; INSTITUCIONES DE INVESTIGACION; FEDERACION DE RUSIA